Developing a Multicultural-Based Sociology Instructional Training Management Model to Improve the Teachers’ Professional Competence in Semarang City - Rochana, Totok; Rachman, Maman; Slamet, Achmad; Rifai, Achmad (The Journal of Educational Development, 2018)
The background of this study is that (1) the characteristics of sociology as subject suggest the need for multicultural-based instruction; (2) teachers have never participated in multicultural-based sociology instructional training; (3) there has not been any multicultural-based sociology instructional training management model. The objectives of this study are (1) to describe the current sociology teacher training management model; (2) to design the development of a multicultural-based sociology instructional training management model; (3) to describe the final form of the multicultural-based sociology instructional training management model. This study employed Research and Development (R & D) approach. Data were collected through interviews, closed and open questionnaires, and documentation studies. The data were then analyzed using descriptive percentages, mean analysis, and qualitative analysis techniques. The results show that (1) the current sociology teacher training management model includes four management functions: training of planning, training of organization, training of implementation, and training of evaluation; (2) the development of a multicultural-based sociology training management model includes three management functions: training of planning, training of implementation, and training of evaluation; (3) the final model of multicultural-based sociology instructional training management includes three management functions: training of planning, training of implementation, and training of evaluation. The conclusion is that the final model of the multicultural-based sociology instructional training management is effectively applied to the sociology teacher.